A highly wear-resistant wood reconstituted material and preparation method thereof
By impregnating the wood recombinant units with low viscosity urea formaldehyde resin and high viscosity melamine modified resin, the problems of poor wear resistance and color limitation of existing wood recombinant materials were solved, and a high wear resistance and multifunctional wood recombinant material was prepared.
Patent Information
- Application Number
- CN202411946758.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The existing wood recombinant materials have poor wear resistance, which limits their application in the fields of tool holders, butt stocks, industrial floors, etc., and the phenolic resin has a dark color, making it difficult to prepare light or colored materials.
The wood recombinant unit is simultaneously impregnated with low viscosity urea formaldehyde resin and high viscosity melamine modified resin. By adjusting the mass ratio of the resin and the preparation process, a high wear-resistant wood recombinant material is prepared.
It improves the wear resistance, hardness and density of wood recombinant materials, can show excellent performance in application scenarios where hard surface contact, and can adjust the color according to needs, broadening the application range.
Smart Images

Figure CN119748580A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wood processing, and in particular relates to a highly wear-resistant wood reconstituted material and a preparation method thereof. Background Art
[0002] Wood reconstituted materials are boards or square materials made by processing wood or bamboo into wood reconstituted units (wood bundles, fiberized wood veneers, thin veneers), and then processed through processes such as resin impregnation, drying, paving, and hot pressing. At present, the resin used to prepare reconstituted materials by hot pressing is mainly low molecular weight phenolic resin for impregnation. The wood reconstituted materials made of this phenolic resin have poor wear resistance, which limits their application in knife handles, gun stocks, industrial floors, textile shuttles, etc. In addition, phenolic resins are dark in color and are difficult to make into light-colored or colored wood reconstituted materials, which limits the application expansion of wood reconstituted materials. Summary of the invention
[0003] In view of the above technical problems, the present invention provides a highly wear-resistant wood reconstituted material and a preparation method thereof.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] One of the objects of the present invention is to provide a highly wear-resistant wood reconstituted material, which is prepared by simultaneously impregnating a wood reconstituted unit with a low-viscosity urea-formaldehyde resin and a high-viscosity melamine modified resin; wherein the mass ratio of the low-viscosity urea-formaldehyde resin to the high-viscosity melamine modified resin is (3-7): (7-3).
[0006] Low-viscosity urea-formaldehyde resin can penetrate well into the interior of the wood recombinant unit, giving the recombinant material good water resistance, strength and rigidity, making it less likely to deform or break when in contact with a hard surface; melamine resin itself has strong wear resistance and bonding properties, and high-viscosity melamine-modified resin is retained in large quantities on the surface of the wood recombinant unit, playing a role in bonding the recombinant unit and significantly improving the wear resistance of the recombinant material surface. Melamine-modified resin not only has good wear resistance, but also exhibits good hardness, which makes it also show excellent performance in application scenarios involving hard surface contact. In addition, both low-viscosity urea-formaldehyde resin and high-viscosity melamine-modified resin are colorless, and pigments can be added as needed to adjust the color.
[0007] Furthermore, the low-viscosity urea-formaldehyde resin comprises the following raw materials, measured by weight: 90-145 parts of formaldehyde aqueous solution, 50-70 parts of urea and 4-8 parts of a modifier.
[0008] Furthermore, the concentration of the formaldehyde aqueous solution is 35-55wt%; and / or
[0009] The modifier is one or more of ethylene glycol, diethylene glycol and dipropylene glycol; and / or
[0010] The low-viscosity urea-formaldehyde resin has a viscosity of 15-35 mPa.s and a solid content of 45-55%.
[0011] Furthermore, the specific preparation steps of the low-viscosity urea-formaldehyde resin include:
[0012] Mix the formaldehyde aqueous solution with the first batch of urea, adjust the pH to 6-8, and keep warm at 80-90°C for 30-60 minutes;
[0013] After the first heat preservation, adjust the pH to 2.5-3.5, add the modifier, and keep warm at 80-90°C for 1-2 hours;
[0014] After the second heat preservation, adjust the pH to 4.5-5.5, add the second batch of urea, and keep warm at 80-90°C for 30-60 minutes;
[0015] After the third heat preservation, the pH is adjusted to 7-8, and the temperature is lowered to room temperature to obtain a low-viscosity urea-formaldehyde resin;
[0016] in,
[0017] The mass ratio of the first batch of urea to the second batch of urea is (28-40): (20-35);
[0018] The molar ratio of the formaldehyde aqueous solution to the first batch of urea is (2.5-3.5):1.
[0019] Furthermore, the high-viscosity melamine-modified resin comprises the following raw materials, measured by weight: 90-145 parts of formaldehyde aqueous solution, 30-50 parts of urea, 40-70 parts of melamine and 5-10 parts of dicyandiamide.
[0020] Furthermore, the high viscosity melamine modified resin has a viscosity of 150-300 mPa.s and a solid content of 50-60%; and / or
[0021] The concentration of the formaldehyde aqueous solution is 35-55 wt %.
[0022] Furthermore, the specific preparation steps of the high-viscosity melamine-modified resin include:
[0023] Mix the formaldehyde aqueous solution, dicyandiamide, the first batch of melamine and the first batch of urea, adjust the pH to 7-9, and keep warm at 80-90° C. for 20-40 minutes;
[0024] After the first heat preservation, adjust the pH to 6.0-6.5 and keep warm at 80-90°C for 3-4 hours;
[0025] After the second heat preservation, adjust the pH to 8.5-9.0, add the second batch of melamine, and keep warm at 80-90°C for 2-3 hours;
[0026] After the third heat preservation, adjust the pH to 9.0-9.5, add the third batch of melamine, and keep warm at 75-85°C for 1-2 hours;
[0027] After the fourth heat preservation, adjust the pH to 9.5-10.0, add the second batch of urea, and keep warm at 65-75°C for 30-60 minutes;
[0028] After the fifth heat preservation, the temperature is lowered to room temperature to obtain a high-viscosity melamine modified resin;
[0029] in,
[0030] The mass ratio of the first batch of melamine, the second batch of melamine and the third batch of melamine is (10-20): (25-35): (5-15);
[0031] The mass ratio of the first batch of urea to the second batch of urea is (25-35):(5-15).
[0032] The second object of the present invention is to provide a method for preparing a highly wear-resistant wood reconstituted material, comprising the following steps:
[0033] A resin mixture is obtained by mixing a low-viscosity urea-formaldehyde resin and a high-viscosity melamine-modified resin;
[0034] After the wood is made into a wood reconstructed unit, it is subjected to a primary drying treatment, and then impregnated in the resin mixture. After the impregnation is completed, it is subjected to a secondary drying treatment, and then balancing treatment, assembly, and hot pressing are performed in sequence to obtain a highly wear-resistant wood reconstructed material.
[0035] Furthermore, the specific preparation steps of the wood reorganization unit include: decomposing the wood into wood fiber bundles with an average diameter of ≤2.5 mm; or peeling the wood into thin veneers with an average thickness of ≤1.7 mm, wherein the wood is poplar, eucalyptus or birch; and / or
[0036] The conditions of the primary drying treatment are: drying the wood recombinant unit to a moisture content of 3-8% and a drying temperature of 90-110° C.; and / or
[0037] The conditions for the impregnation are: an impregnation time of 30-90 minutes and a glue amount of 15-30 wt %; and / or
[0038] The conditions of the secondary drying treatment are: drying the wood recombinant unit to a moisture content of 8-15% and a drying temperature of 50-70° C.; and / or
[0039] The conditions of the balance treatment are: the moisture content of the wood recombinant unit is 8-15%, and the moisture content deviation between the wood recombinant units is controlled within 5%; and / or
[0040] The hot pressing conditions are: hot pressing temperature 105-125° C., hot pressing time 60-90 minutes, hot pressing pressure 5-15 MPa; and / or
[0041] The density of the highly wear-resistant wood reconstituted material is 1.25-1.35 g / cm 3 .
[0042] The third object of the present invention is to provide a highly wear-resistant wood reconstructed material for use in knife handles, gun stocks, industrial floors and wooden shuttles for textiles.
[0043] Compared with the prior art, the present invention has the following advantages and technical effects:
[0044] The high wear-resistant wood reconstituted material prepared by the invention has high density, large glue amount, high hardness and good wear resistance.
[0045] The invention uses light-colored urea-formaldehyde resin and melamine-modified resin to prepare the wood recombinant material, and can prepare wood recombinant materials of various colors or colors according to needs, thereby greatly broadening the application range of the wood recombinant material. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0047] Figure 1 This is a physical picture of the highly wear-resistant wood reconstituted material prepared in Example 8;
[0048] Figure 2 This is a comparison of the appearance of the poplar wood (A) and the highly wear-resistant wood reconstructed material (B) prepared in Example 8 after wear resistance testing;
[0049] Figure 3 This is a comparison diagram of the poplar wood (A) and the highly wear-resistant wood reconstructed material (B) prepared in Example 8 after wear resistance testing under ultra-depth microscope;
[0050] Figure 4 The scanning electron microscope comparison diagram of the poplar wood (A) and the highly wear-resistant wood reconstructed material (B) prepared in Example 8 after wear resistance test;
[0051] Figure 5 This is a physical picture of the highly wear-resistant wood reconstituted material prepared in Example 9. DETAILED DESCRIPTION
[0052] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0053] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0054] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0055] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0056] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0057] The embodiment of the present invention simultaneously impregnates wood recombinant units with low-viscosity urea-formaldehyde resin and high-viscosity melamine modified resin, and manufactures highly wear-resistant wood recombinant materials through drying, assembly, and high-pressure hot pressing, including (i) resin synthesis; (ii) preparation of wood recombinant units; (iii) primary drying of wood recombinant units; (iv) gluing of wood recombinant units; (v) secondary drying of wood recombinant units; (vi) balancing treatment of wood recombinant units; (vii) assembly of wood recombinant units; and (viii) hot pressing of wood recombinant materials.
[0058] The embodiment of the present invention discloses a method for preparing a highly wear-resistant wood reconstituted material, which specifically comprises the following steps:
[0059] (i) Resin synthesis: mixing low-viscosity urea-formaldehyde resin and high-viscosity melamine-modified resin to obtain a resin mixture;
[0060] (ii) Preparation of wooden recombinant units: using special deflaking equipment to deflake the wood into wood fiber bundles with an average diameter of ≤2.5 mm; or peeling the wood into thin veneers with an average thickness of ≤1.7 mm;
[0061] (iii) Primary drying of the wood recombinant unit: drying the wood recombinant unit using drying equipment until the moisture content is 3-8% and the drying temperature is 90-110°C;
[0062] (iv) Gluing of wood recombinant unit: adding the resin mixture in step (i) into a dipping tank, placing the wood recombinant unit in step (iii) into the dipping tank and dipping for 30-90 minutes, with a glue application amount of 15-30%;
[0063] The present invention improves the strength and uniformity of wood by applying glue, so that wood fiber bundles are combined with synthetic resin to form a new organic whole, thereby improving the overall performance of the material. A large amount of glue can significantly increase the amount of glue remaining on the surface of the reconstructed material after hot pressing, thereby improving the hardness and wear resistance of the reconstructed material. Moreover, a large amount of glue can effectively improve the bonding performance between reconstructed units and improve the dimensional stability of the reconstructed material. During the gluing process, the resin fills the micropores in the pits and cell walls, changes the penetration channels of wood and bamboo, and thus improves the water resistance and dimensional stability of the material.
[0064] (V) Secondary drying of wood recombinant unit: Dry the wood recombinant unit to a moisture content of 8-15% at a drying temperature of 50-70°C using drying equipment;
[0065] (VI) Balancing treatment of wood recombinant units: The wood recombinant units are balanced in a balancing room or storage bin until the moisture content of the wood recombinant units is 8-15%, and the moisture content deviation between the wood recombinant units is controlled within 5%;
[0066] (VII) Assembling wooden recombinant units: Laying wooden recombinant units flat on a laying table along the grain;
[0067] (VIII) Hot pressing of wood reconstituted materials: the laid reconstituted material slab is sent into a hot press for hot pressing and molding. The molding process is as follows: hot pressing temperature 105-125°C, hot pressing time 60-90 minutes, hot pressing pressure 5-15MPa.
[0068] The density of the highly wear-resistant wood reconstituted material obtained by the preparation method is 1.25-1.35 g / cm 3 For example, in the following embodiments of the present invention, the density of the highly wear-resistant wood reconstituted material is 1.25 g / cm 3 , 1.30g / cm 3 , 1.35g / cm 3Or any value between the aforementioned ranges. By increasing the density, the wood reconstituted material can significantly enhance its surface Jin's hardness and Brinell hardness. The increase in density means that the material is denser, thereby improving the material's load-bearing capacity and wear resistance.
[0069] In some embodiments of the present invention, in step (i), the mass ratio of the low-viscosity urea-formaldehyde resin to the high-viscosity melamine-modified resin is (3-7): (7-3), preferably (4-6): (6-4). Exemplarily, in the following embodiments of the present invention, the mass ratio of the low-viscosity urea-formaldehyde resin to the high-viscosity melamine-modified resin is 3:7, 5:5, 7:3 or any ratio between the aforementioned ratios.
[0070] The low-viscosity urea-formaldehyde resin comprises the following raw materials, calculated by weight: 90-145 parts of formaldehyde aqueous solution, 50-70 parts of urea and 4-8 parts of modifier. Exemplarily, the low-viscosity urea-formaldehyde resin comprises 50 parts, 60 parts, 70 parts of urea or any range or sub-range between the aforementioned proportions; the low-viscosity urea-formaldehyde resin comprises 4 parts, 6 parts, 8 parts of modifier or any range or sub-range between the aforementioned proportions.
[0071] The concentration of the formaldehyde aqueous solution in the low-viscosity urea-formaldehyde resin can be 35-55wt%, but in the art, the more commonly used concentration is 50wt%, so the present invention takes the concentration of the formaldehyde aqueous solution in the low-viscosity urea-formaldehyde resin as 50wt% as an example for experimentation, and correspondingly, the amount of the formaldehyde aqueous solution is selected as 100 parts. As the concentration changes, the amount will also change accordingly, and the appropriate concentration and amount can be selected according to different environments.
[0072] The modifier in the low-viscosity urea-formaldehyde resin is one or more of ethylene glycol, diethylene glycol and dipropylene glycol; illustratively, in the following embodiments of the present invention, the modifier can be selected from ethylene glycol, diethylene glycol or dipropylene glycol.
[0073] The specific preparation steps of the low-viscosity urea-formaldehyde resin include:
[0074] Mixing the formaldehyde aqueous solution with the first batch of urea, adjusting the pH to 6-8 (e.g., pH 6, 7 or 8), and keeping the mixture at 80-90° C. (e.g., 80° C., 85° C. or 90° C.) for 30-60 minutes (e.g., 30 minutes, 45 minutes or 60 minutes);
[0075] After the first heat preservation, adjust the pH to 2.5-3.5 (such as pH = 2.5, 3.0 or 3.5), add the modifier, and keep the mixture at 80-90° C. (such as 80° C., 85° C. or 90° C.) for 1-2 hours (such as 1 hour, 1.5 hours or 2 hours);
[0076] After the second heat preservation, adjust pH=4.5-5.5 (such as pH=4.5, 5.0 or 5.5), add the second batch of urea, and keep warm at 80-90° C. (such as 80° C., 85° C. or 90° C.) for 30-60 minutes (such as 30 minutes, 45 minutes or 60 minutes);
[0077] After the third heat preservation, adjust the pH to 7-8 (such as pH = 7.0, 7.5 or 8.0), and lower the temperature to room temperature to obtain a low-viscosity urea-formaldehyde resin;
[0078] In the preparation process of low-viscosity urea-formaldehyde resin, the mass ratio of the first batch of urea to the second batch of urea is (28-40):(20-35); illustratively, in the following embodiments of the present invention, the mass ratio of the first batch of urea to the second batch of urea can be selected as 28.6:21.4, 33.3:26.7, 40:30 or any ratio between the foregoing ratios.
[0079] In the preparation process of the low-viscosity urea-formaldehyde resin, the molar ratio of the formaldehyde aqueous solution (mass concentration is 35-50wt%) to the first batch of urea is (2.5-3.5) : 1. Exemplarily, in the following embodiments of the present invention, the molar ratio of the formaldehyde aqueous solution to the first batch of urea can be selected as 2.5: 1, 3: 1, 3.5: 1 or any ratio between the aforementioned ratios.
[0080] The viscosity of the low-viscosity urea-formaldehyde resin prepared by the above method is 15-35 mPa.s (such as 15 mPa.s, 25 mPa.s or 35 mPa.s), and the solid content is 45-55% (such as 45%, 50% or 55%). The solid content is mainly achieved by adjusting the concentration of the formaldehyde aqueous solution and the amount of water added. Therefore, for example, the low-viscosity urea-formaldehyde resin of the present invention can also include the following raw materials in parts by mass: 100 parts of formaldehyde aqueous solution, 50-70 parts of urea, 4-8 parts of modifier and 15-30 parts of water (such as 15 parts, 25 parts or 30 parts).
[0081] The high-viscosity melamine-modified resin comprises the following raw materials in parts by mass: 90-145 parts of formaldehyde aqueous solution, 30-50 parts of urea, 40-70 parts of melamine and 5-10 parts of dicyandiamide. Exemplarily, the high-viscosity melamine-modified resin comprises 30 parts, 40 parts, 50 parts or any range or sub-range between the aforementioned proportions of urea; the high-viscosity melamine-modified resin comprises 40 parts, 50 parts, 60 parts, 70 parts or any range or sub-range between the aforementioned proportions of melamine; the high-viscosity melamine-modified resin comprises 5 parts, 7.5 parts, 10 parts or any range or sub-range between the aforementioned proportions of dicyandiamide.
[0082] The concentration of the formaldehyde aqueous solution in the high-viscosity melamine modified resin can be 35-55wt%, but in the art, the more commonly used concentration is 50wt%, so the present invention takes the concentration of the formaldehyde aqueous solution in the high-viscosity melamine modified resin as 50wt% as an example for experimentation, and correspondingly, the amount of the formaldehyde aqueous solution is selected as 100 parts. As the concentration changes, the amount will also change accordingly, and the appropriate concentration and amount can be selected according to different environments.
[0083] The specific preparation steps of the high-viscosity melamine-modified resin include:
[0084] Mixing the formaldehyde aqueous solution, dicyandiamide, the first batch of melamine and the first batch of urea, adjusting the pH to 7-9 (e.g., 7.0, 7.5, 8.0 or 9.0), and keeping the mixture at 80-90° C. (e.g., 80° C., 85° C. or 90° C.) for 20-40 minutes (e.g., 20 minutes, 30 minutes or 40 minutes);
[0085] After the first incubation, adjust the pH to 6.0-6.5 (e.g., 6.0, 6.2, or 6.5), and incubate at 80-90° C. (e.g., 80° C., 85° C., or 90° C.) for 3-4 hours (e.g., 3 hours, 3.5 hours, or 4 hours);
[0086] After the second heat preservation, adjust the pH to 8.5-9.0 (such as 8.5, 8.7 or 9.0), add the second batch of melamine, and keep the mixture at 80-90° C. (such as 80° C., 85° C. or 90° C.) for 2-3 hours (such as 2 hours, 2.5 hours or 3 hours);
[0087] After the third heat preservation, adjust the pH to 9.0-9.5 (such as 9.0, 9.2 or 9.5), add the third batch of melamine, and keep the temperature at 75-85° C. (such as 75° C., 80° C. or 85° C.) for 1-2 hours (such as 1 hour, 1.5 hours or 2 hours);
[0088] After the fourth heat preservation, adjust the pH to 9.5-10.0 (such as 9.5, 9.7 or 10.0), add the second batch of urea, and keep warm at 65-75° C. (such as 65° C., 70° C. or 75° C.) for 30-60 minutes (such as 30 minutes, 45 minutes or 60 minutes);
[0089] After the fifth heat preservation, the temperature is lowered to room temperature to obtain a high-viscosity melamine-modified resin;
[0090] In the preparation process of the high-viscosity melamine-modified resin, the mass ratio of the first batch of melamine, the second batch of melamine and the third batch of melamine is (10-20):(25-35):(5-15); illustratively, in the following embodiments of the present invention, the mass ratio of the first batch of melamine, the second batch of melamine and the third batch of melamine is 10:25:5, 15:30:15, 20:35:15, 15:30:5 or any ratio between the foregoing ratios.
[0091] In the preparation process of the high-viscosity melamine-modified resin, the mass ratio of the first batch of urea to the second batch of urea is (25-35):(5-15). Exemplarily, in the following embodiments of the present invention, the mass ratio of the first batch of urea to the second batch of urea is 35:15, 30:10, 25:5 or any ratio between the aforementioned ratios.
[0092] The high-viscosity melamine modified resin prepared by the above method has a viscosity of 150-300 mPa.s (such as 150 mPa.s, 200 mPa.s, 225 mPa.s or 300 mPa.s) and a solid content of 50-60% (such as 50%, 54%, 55% or 60%). The solid content is mainly achieved by regulating the concentration of the formaldehyde aqueous solution and the amount of water added. Therefore, for example, the high-viscosity melamine modified resin of the present invention can also include the following raw materials in parts by mass: 100 parts of formaldehyde aqueous solution, 30-50 parts of urea, 40-70 parts of melamine, 5-10 parts of dicyandiamide and 20-55 parts of water (such as 20 parts, 25 parts, 40 parts or 55 parts).
[0093] In the following examples of the present invention, either formic acid or ammonium sulfate can be used to adjust the pH value, and the specific choice does not affect the product performance.
[0094] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0095] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.
[0096] The raw materials used in the present invention are all purchased from the market.
[0097] The technical solution of the present invention is further illustrated by the following embodiments.
[0098] Example 1
[0099] A preparation method of a low-viscosity urea-formaldehyde resin: 100 kg of a 50wt% formaldehyde aqueous solution, 28.6 kg of urea and 30 kg of water are added to a reaction kettle, the pH is adjusted to 6.0, and the mixture is kept at 90°C for 30 minutes. After the heat preservation is completed, the pH is adjusted to 2.5, 4 kg of ethylene glycol is added, and the mixture is kept at 90°C for 1 hour. After the heat preservation is completed, the pH is adjusted to 4.5, 21.4 kg of urea is added, and the mixture is kept at 90°C for another 30 minutes. After the heat preservation is completed, the pH is adjusted to 7.0, and the temperature is lowered to room temperature to obtain a low-viscosity urea-formaldehyde resin having a resin viscosity of 15 mPa.s and a solid content of 45%.
[0100] Example 2
[0101] A preparation method of a low-viscosity urea-formaldehyde resin: 100 kg of a 50wt% formaldehyde aqueous solution, 33.3 kg of urea and 25 kg of water are added to a reaction kettle, the pH is adjusted to 7.0, and the mixture is kept at 85°C for 45 minutes. After the heat preservation is completed, the pH is adjusted to 3.0, 6 kg of diethylene glycol is added, and the mixture is kept at 85°C for 1.5 hours. After the heat preservation is completed, the pH is adjusted to 5.0, 26.7 kg of urea is added, and the mixture is kept at 85°C for another 45 minutes. After the heat preservation is completed, the pH is adjusted to 7.5, and the temperature is lowered to room temperature to obtain a low-viscosity urea-formaldehyde resin having a resin viscosity of 25 mPa.s and a solid content of 50%.
[0102] Example 3
[0103] A preparation method of a low-viscosity urea-formaldehyde resin: 100 kg of a 50 wt% formaldehyde aqueous solution, 40 kg of urea and 15 kg of water are added to a reaction kettle, the pH is adjusted to 8, the mixture is kept at 80°C for 60 minutes, the pH is adjusted to 3.5 after the heat preservation is completed, 8 kg of dipropylene glycol is added, the mixture is kept at 80°C for 2 hours, the pH is adjusted to 5.5 after the heat preservation is completed, 30 kg of urea is added, the mixture is kept at 80°C for another 60 minutes, the pH is adjusted to 8.0 after the heat preservation is completed, and the low-viscosity urea-formaldehyde resin is obtained, wherein the resin viscosity is 35 mPa.s and the solid content is 55%.
[0104] Example 4
[0105] A preparation method of a high-viscosity melamine modified resin comprises the following steps: adding 100 kg of a 50 wt% formaldehyde aqueous solution, 10 kg of dicyandiamide, 10 kg of melamine, 35 kg of urea and 55 kg of water into a reaction kettle, adjusting the pH to 7.0, keeping the mixture at 80°C for 20 minutes, adjusting the pH to 6.0 after the temperature is maintained at 80°C for 3 hours, adjusting the pH to 8.5 after the temperature is maintained, adding 25 kg of melamine, keeping the mixture at 80°C for 2 hours, adjusting the pH to 9.0 after the temperature is maintained, adding 5 kg of melamine, keeping the mixture at 75°C for 1 hour, adjusting the pH to 9.5, adding 15 kg of urea, keeping the mixture at 65°C for 30 minutes, cooling the mixture to room temperature, and obtaining a high-viscosity melamine modified resin having a resin viscosity of 150 mPa.s and a solid content of 50%.
[0106] Example 5
[0107] A preparation method of a high-viscosity melamine modified resin comprises the following steps: adding 100 kg of a 50 wt% formaldehyde aqueous solution, 7.5 kg of dicyandiamide, 15 kg of melamine, 30 kg of urea and 40 kg of water into a reaction kettle, adjusting the pH to 8.0, keeping the mixture at 85°C for 30 minutes, adjusting the pH to 6.2 after the temperature is maintained for 3.5 hours, adjusting the pH to 8.7 after the temperature is maintained, adding 30 kg of melamine, keeping the mixture at 85°C for 2.5 hours, adjusting the pH to 9.2 after the temperature is maintained, adding 15 kg of melamine, keeping the mixture at 80°C for 1.5 hours, adjusting the pH to 9.7 after the temperature is maintained, adding 10 kg of urea, keeping the mixture at 70°C for 45 minutes, cooling the mixture to room temperature, and obtaining a high-viscosity melamine modified resin having a resin viscosity of 225 mPa.s and a solid content of 55%.
[0108] Example 6
[0109] A preparation method for a high-viscosity melamine modified resin comprises the following steps: adding 100 kg of a 50 wt% formaldehyde aqueous solution, 5 kg of dicyandiamide, 20 kg of melamine, 25 kg of urea and 20 kg of water into a reaction kettle, adjusting the pH to 9.0, keeping the mixture at 90°C for 40 minutes, adjusting the pH to 6.5 after the temperature is maintained for 4 hours, adjusting the pH to 9.0 after the temperature is maintained, adding 35 kg of melamine, keeping the mixture at 90°C for 3 hours, adjusting the pH to 9.5 after the temperature is maintained, adding 15 kg of melamine, keeping the mixture at 85°C for 2 hours, adjusting the pH to 10.0, adding 5 kg of urea, keeping the mixture at 75°C for 60 minutes, cooling the mixture to room temperature, and obtaining a high-viscosity melamine modified resin having a resin viscosity of 300 mPa.s and a solid content of 60%.
[0110] Example 7
[0111] A preparation method for a high-viscosity melamine modified resin comprises the following steps: adding 100 kg of a 50 wt% formaldehyde aqueous solution, 7.5 kg of dicyandiamide, 15 kg of melamine, 30 kg of urea and 25 kg of water into a reaction kettle, adjusting the pH to 7.5, keeping the mixture at 85°C for 30 minutes, adjusting the pH to 6.2 after the heat preservation is completed, and continuing to keep the mixture at 85°C for 4 hours. After the heat preservation is completed, adjusting the pH to 8.7, adding 30 kg of melamine, keeping the mixture at 85°C for 3 hours, and after the heat preservation is completed, adjusting the pH to 9.2, adding 5 kg of melamine, keeping the mixture at 80°C for 1 hour, and after the heat preservation is completed, adjusting the pH to 9.7, adding 10 kg of urea, keeping the mixture at 70°C for 45 minutes, and after the heat preservation is completed, cooling the mixture to room temperature to obtain a high-viscosity melamine modified resin having a resin viscosity of 200 mPa.s and a solid content of 54%.
[0112] Example 8
[0113] Preparation of a highly wear-resistant wood reconstituted material:
[0114] (i) Resin synthesis: The low-viscosity urea-formaldehyde resin prepared in Example 2 and the high-viscosity melamine-modified resin prepared in Example 5 were mixed at a mass ratio of 5:5 to obtain a resin mixture;
[0115] (ii) Preparation of wooden recombinant units: Poplar wood is deflaked into wood fiber bundles with an average diameter of 2.5 mm using a special deflaking device;
[0116] (iii) Primary drying of the wood recombinant unit: drying the wood recombinant unit using drying equipment until the moisture content is 5% and the drying temperature is 110° C.;
[0117] (iv) Gluing of wood recombinant unit: add the resin mixture in step (i) into a dipping tank, put the wood recombinant unit in step (iii) into the dipping tank and immerse for 60 minutes, with a glue application amount of 30%;
[0118] (V) Secondary drying of wood recombinant units: Dry the wood recombinant units to a moisture content of 12% using drying equipment at a drying temperature of 60°C;
[0119] (VI) Balancing treatment of wood recombinant units: The wood recombinant units are balanced in a balancing room until the moisture content of the wood recombinant units is 12% and the moisture content deviation between the wood recombinant units is controlled within 5%;
[0120] (VII) Assembling wooden recombinant units: Laying wooden recombinant units flat on a laying table along the grain;
[0121] (VIII) Hot pressing of wood reconstituted materials: The laid reconstituted material slab is sent into a hot press for hot pressing. The molding process is as follows: hot pressing temperature 115°C, hot pressing time 75 minutes, hot pressing pressure 10 MPa, and the density is 1.30 g / cm3 Highly wear-resistant wood reconstructed material.
[0122] Example 9
[0123] Preparation of a highly wear-resistant wood reconstituted material:
[0124] (i) Resin synthesis: The low-viscosity urea-formaldehyde resin prepared in Example 1 and the high-viscosity melamine-modified resin prepared in Example 4 were mixed at a mass ratio of 3:7 to obtain a resin mixture;
[0125] (ii) Preparation of wooden recombinant units: using a special deflaking device to deflake the eucalyptus into wood fiber bundles with an average diameter of 1.5 mm;
[0126] (iii) Primary drying of the wood recombinant unit: drying the wood recombinant unit using drying equipment until the moisture content is 8% and the drying temperature is 100° C.;
[0127] (iv) Gluing of wood recombinant unit: add the resin mixture in step (i) into the dipping tank, put the wood recombinant unit in step (iii) into the dipping tank and immerse for 30 minutes, the glue amount is 25%;
[0128] (V) Secondary drying of wood recombinant units: Dry the wood recombinant units to a moisture content of 10% using drying equipment at a drying temperature of 70°C;
[0129] (VI) Balancing treatment of wood recombinant units: The wood recombinant units are balanced in the storage bin until the moisture content of the wood recombinant units is 14%, and the moisture content deviation between the wood recombinant units is controlled within 5%;
[0130] (VII) Assembling wooden recombinant units: Laying wooden recombinant units flat on a laying table along the grain;
[0131] (VIII) Hot pressing of wood reconstituted materials: The laid reconstituted material slab is sent into a hot press for hot pressing. The molding process is as follows: hot pressing temperature 125°C, hot pressing time 60 minutes, hot pressing pressure 15 MPa, and the density is 1.35 g / cm 3 Highly wear-resistant wood reconstructed material.
[0132] Example 10
[0133] Preparation of a highly wear-resistant wood reconstituted material:
[0134] (i) Resin synthesis: The low-viscosity urea-formaldehyde resin prepared in Example 3 and the high-viscosity melamine-modified resin prepared in Example 6 were mixed at a mass ratio of 7:3 to obtain a resin mixture;
[0135] (ii) Preparation of wooden recombinant units: Birch wood was rotary cut into thin veneers with an average thickness of 1.7 mm;
[0136] (iii) Primary drying of the wood recombinant unit: drying the wood recombinant unit using drying equipment until the moisture content is 3% and the drying temperature is 90° C.;
[0137] (iv) Gluing of wood recombinant unit: add the resin mixture in step (i) into a dipping tank, put the wood recombinant unit in step (iii) into the dipping tank and immerse for 90 minutes, with a glue application amount of 15%;
[0138] (V) Secondary drying of wood recombinant units: Dry the wood recombinant units using drying equipment to a moisture content of 8% at a drying temperature of 50°C;
[0139] (VI) Balancing treatment of wood recombinant units: The wood recombinant units are balanced in a balancing room or storage bin until the moisture content of the wood recombinant units is 8%, and the moisture content deviation between the wood recombinant units is controlled within 5%;
[0140] (VII) Assembling wooden recombinant units: Laying wooden recombinant units flat on a laying table along the grain;
[0141] (VIII) Hot pressing of wood reconstituted materials: The laid reconstituted material slab is sent into a hot press for hot pressing. The molding process is as follows: hot pressing temperature 105°C, hot pressing time 90 minutes, hot pressing pressure 5MPa, and the density is 1.25g / cm 3 Highly wear-resistant wood reconstructed material.
[0142] Embodiment 11
[0143] Preparation of a highly wear-resistant wood reconstituted material:
[0144] (i) Resin synthesis: The low-viscosity urea-formaldehyde resin prepared in Example 2 and the high-viscosity melamine-modified resin prepared in Example 7 were mixed at a mass ratio of 5:5 to obtain a resin mixture;
[0145] (ii) Preparation of wooden recombinant units: Poplar wood was rotary cut into thin veneers with an average thickness of 1.2 mm;
[0146] (iii) Primary drying of the wood recombinant unit: drying the wood recombinant unit using drying equipment until the moisture content is 6% and the drying temperature is 100°C;
[0147] (iv) Gluing of wood recombinant unit: add the resin mixture in step (i) into a dipping tank, put the wood recombinant unit in step (iii) into the dipping tank and immerse for 60 minutes, with a glue application amount of 20%;
[0148] (V) Secondary drying of wood recombinant units: Dry the wood recombinant units to a moisture content of 10% using drying equipment at a drying temperature of 60°C;
[0149] (VI) Balancing treatment of wood recombinant units: The wood recombinant units are balanced in the storage bin until the moisture content of the wood recombinant units is 12% and the moisture content deviation between the wood recombinant units is controlled within 5%;
[0150] (VII) Assembling wooden recombinant units: Laying wooden recombinant units flat on a laying table along the grain;
[0151] (VIII) Hot pressing of wood reconstituted materials: The laid reconstituted material slab is sent into a hot press for hot pressing. The molding process is as follows: hot pressing temperature 115°C, hot pressing time 75 minutes, hot pressing pressure 10 MPa, and the density is 1.30 g / cm 3 Highly wear-resistant wood reconstructed material.
[0152] Comparative Example 1
[0153] The same as Example 8, except that the high-viscosity melamine-modified resin in step (i) is removed, that is, the high-viscosity melamine-modified resin is replaced by low-viscosity urea-formaldehyde resin.
[0154] Comparative Example 2
[0155] The same as Example 8, except that the low-viscosity urea-formaldehyde resin in step (i) is removed, that is, the low-viscosity urea-formaldehyde resin is replaced by a high-viscosity melamine-modified resin.
[0156] Comparative Example 3
[0157] Same as Example 11, except that in step (i), the low-viscosity urea-formaldehyde resin and the high-viscosity melamine-modified resin are mixed in a mass ratio of 9:1.
[0158] Comparative Example 4
[0159] Same as Example 11, except that the high-viscosity melamine-modified resin in step (i) is replaced by a melamine-modified resin for plywood purchased from the prior art, with a resin viscosity of 110 cps and a solid content of 55%.
[0160] Comparative Example 5
[0161] Same as Example 11, except that the low-viscosity urea-formaldehyde resin in step (I) is replaced with a urea-formaldehyde resin for plywood purchased from the prior art, with a resin viscosity of 84 cps and a solid content of 50%.
[0162] Comparative Example 6
[0163] Same as Example 11, except that the poplar wood in step (ii) is replaced by pine wood.
[0164] Comparative Example 7
[0165] Same as Example 11, except that step (iv) is: adding the resin mixture in step (i) into a dipping tank, placing the wood recombinant unit in step (iii) into the dipping tank and dipping for 20 minutes, with a gluing amount of 10%.
[0166] Comparative Example 8
[0167] Same as Example 11, except that, step (eight) is: feeding the laid reconstituted material slab into a hot press for hot pressing, and the molding process is: hot pressing temperature 115°C, hot pressing time 75 minutes, hot pressing pressure 2.5 MPa, and obtaining a density of 1.15 g / cm 3 Highly wear-resistant wood reconstructed material.
[0168] Performance Test:
[0169] The King's hardness test is in accordance with GB / T 1941-2021 "Test methods for physical and mechanical properties of small defect-free wood specimens Part 19: Determination of hardness".
[0170] The Brinell hardness test is conducted in accordance with Japanese standard JIS Z2101-2009 “Test methods for wood”.
[0171] The wear thickness is tested using an abrasion tester in accordance with GB / T 17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels 4.45".
[0172] The water absorption thickness expansion rate is tested in accordance with GB / T 17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels 4.4".
[0173] The test results are shown in Table 1.
[0174] Table 1
[0175]
[0176]
[0177] It can be seen from Table 1 that the wood reconstituted materials prepared in Examples 8-11 of the present invention have high hardness and good wear resistance.
[0178] Figure 1 This is a physical picture of the highly wear-resistant wood reconstituted material prepared in Example 8.
[0179] Figure 2This is a comparison of the appearances of poplar solid wood (A) and the highly wear-resistant wood reconstructed material (B) prepared in Example 8 after wear resistance testing. It can be seen from the figure that after the wear resistance test, the wear marks of the highly wear-resistant wood reconstructed material prepared in Example 8 are relatively shallow, while the wear marks of the poplar solid wood are relatively obvious, indicating that the wear resistance of the highly wear-resistant wood reconstructed material is significantly better than that of the poplar solid wood.
[0180] Figure 3 This is a super-depth microscope comparison of poplar solid wood (A) and the highly wear-resistant wood reconstructed material (B) prepared in Example 8 after wear resistance test. It can be seen from the figure that after the wear resistance test, the wear depth of the surface of the highly wear-resistant wood reconstructed material prepared in Example 8 is shallow, while the wear depth of the surface of the poplar solid wood is deep, indicating that the wear resistance of the highly wear-resistant wood reconstructed material is significantly better than that of the poplar solid wood
[0181] Figure 4 The scanning electron microscope comparison diagram of the poplar solid wood (A) and the highly wear-resistant wood reconstructed material (B) prepared in Example 8 after the wear resistance test. It can be seen from the figure that after the wear resistance test, the surface of the highly wear-resistant wood reconstructed material prepared in Example 8 is smooth, while the surface of the poplar solid wood has more burrs, indicating that the wear resistance of the highly wear-resistant wood reconstructed material is significantly better than that of the poplar solid wood
[0182] Figure 5 This is a physical picture of the highly wear-resistant wood reconstituted material prepared in Example 9.
[0183] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A highly wear-resistant wood reconstituted material, characterized in that: The invention is prepared by simultaneously impregnating a wood recombinant unit with a low-viscosity urea-formaldehyde resin and a high-viscosity melamine-modified resin; wherein the mass ratio of the low-viscosity urea-formaldehyde resin to the high-viscosity melamine-modified resin is (3-7):(7-3); the viscosity of the low-viscosity urea-formaldehyde resin is 15-35 mPa.s; and the viscosity of the high-viscosity melamine-modified resin is 150-300 mPa.s.
2. The highly wear-resistant wood reconstituted material according to claim 1, characterized in that: The low-viscosity urea-formaldehyde resin comprises the following raw materials, calculated by weight: 90-145 parts of formaldehyde aqueous solution, 50-70 parts of urea and 4-8 parts of a modifier.
3. The highly wear-resistant wood reconstituted material according to claim 2, characterized in that: The concentration of the formaldehyde aqueous solution is 35-55wt%; and / or The modifier is one or more of ethylene glycol, diethylene glycol and dipropylene glycol.
4. The highly wear-resistant wood reconstituted material according to any one of claims 1 to 3, characterized in that: The specific preparation steps of the low-viscosity urea-formaldehyde resin include: Mix the formaldehyde aqueous solution with the first batch of urea, adjust the pH to 6-8, and keep warm at 80-90°C for 30-60 minutes; After the first heat preservation, adjust the pH to 2.5-3.5, add the modifier, and keep warm at 80-90°C for 1-2 hours; After the second heat preservation, adjust the pH to 4.5-5.5, add the second batch of urea, and keep warm at 80-90°C for 30-60 minutes; After the third heat preservation, the pH is adjusted to 7-8, and the temperature is lowered to room temperature to obtain a low-viscosity urea-formaldehyde resin; in, The mass ratio of the first batch of urea to the second batch of urea is (28-40): (20-35); The solid content of the low-viscosity urea-formaldehyde resin is 45-55%.
5. The highly wear-resistant wood reconstituted material according to claim 1, characterized in that: The high-viscosity melamine-modified resin comprises the following raw materials, calculated by weight: 90-145 parts of formaldehyde aqueous solution, 30-50 parts of urea, 40-70 parts of melamine and 5-10 parts of dicyandiamide.
6. The highly wear-resistant wood reconstituted material according to claim 5, characterized in that: The concentration of the formaldehyde aqueous solution is 35-55 wt %.
7. The highly wear-resistant wood reconstituted material according to any one of claims 1, 5-6, characterized in that: The specific preparation steps of the high-viscosity melamine-modified resin include: Mix the formaldehyde aqueous solution, dicyandiamide, the first batch of melamine and the first batch of urea, adjust the pH to 7-9, and keep warm at 80-90° C. for 20-40 minutes; After the first heat preservation, adjust the pH to 6.0-6.5 and keep warm at 80-90°C for 3-4 hours; After the second heat preservation, adjust the pH to 8.5-9.0, add the second batch of melamine, and keep warm at 80-90°C for 2-3 hours; After the third heat preservation, adjust the pH to 9.0-9.5, add the third batch of melamine, and keep warm at 75-85°C for 1-2 hours; After the fourth heat preservation, adjust the pH to 9.5-10.0, add the second batch of urea, and keep warm at 65-75°C for 30-60 minutes; After the fifth heat preservation, the temperature is lowered to room temperature to obtain a high-viscosity melamine modified resin; in, The mass ratio of the first batch of melamine, the second batch of melamine and the third batch of melamine is (10-20): (25-35): (5-15); The mass ratio of the first batch of urea to the second batch of urea is (25-35): (5-15); The solid content of the high-viscosity melamine modified resin is 50-60%.
8. A method for preparing a highly wear-resistant wood reconstituted material according to any one of claims 1 to 7, characterized in that: The following steps are involved: A resin mixture is obtained by mixing a low-viscosity urea-formaldehyde resin and a high-viscosity melamine-modified resin; After the wood is made into a wood reconstructed unit, it is subjected to a primary drying treatment, and then impregnated in the resin mixture. After the impregnation is completed, it is subjected to a secondary drying treatment, and then balancing treatment, assembly, and hot pressing are performed in sequence to obtain a highly wear-resistant wood reconstructed material.
9. The method for preparing a highly wear-resistant wood reconstituted material according to claim 8, characterized in that: The specific preparation steps of the wood reorganization unit include: decomposing the wood into wood fiber bundles with an average diameter of ≤2.5 mm; or peeling the wood into thin veneers with an average thickness of ≤1.7 mm, wherein the wood is poplar, eucalyptus or birch; and / or The conditions of the primary drying treatment are: drying the wood recombinant unit to a moisture content of 3-8% and a drying temperature of 90-110° C.; and / or The conditions for the impregnation are: an impregnation time of 30-90 minutes and a glue amount of 15-30 wt %; and / or The conditions of the secondary drying treatment are: drying the wood recombinant unit to a moisture content of 8-15% and a drying temperature of 50-70° C.; and / or The conditions of the balance treatment are: the moisture content of the wood recombinant unit is 8-15%, and the moisture content deviation between the wood recombinant units is controlled within 5%; and / or The hot pressing conditions are: hot pressing temperature 105-125° C., hot pressing time 60-90 minutes, hot pressing pressure 5-15 MPa; and / or The density of the highly wear-resistant wood reconstituted material is 1.25-1.35 g / cm 3 .
10. Use of the highly wear-resistant wood reconstructed material according to any one of claims 1 to 7 in knife handles, gun stocks, industrial floors and wooden shuttles for textiles.
Citation Information
Cited By
Sound-insulation fireproof building material and preparation method thereof
CN121061991A